DNA adducts in human placenta as related to air pollution and to GSTM1 genotype - Topinka, J; Binková, B; Mracková, G; Stávková, Z; Benes, I; Dejmek, J; Lenícek, J; Srám, R J (Mutation research, 1997)
DNA adducts in human placenta have been studied in relation to metabolic genotype for glutathione S-transferase M1 (GSTM1) in 98 mothers living in two regions with a different annual average air pollution levels: Northern Bohemia-the district of Teplice as polluted industrial area (mines, brown coal power plants) and Southern Bohemia-the district of Prachatice as agricultural area without heavy industry. Forty-nine placenta samples (25 from the Teplice district and 24 from the Prachatice district) from non-smoking mothers with the date of delivery in the summer period and 49 placenta samples (25 from the Teplice district and 24 from Prachatice district) from mothers with the date of delivery in the winter period were analysed. The total DNA adduct levels were calculated as the sum of adducts in the diagnoal radioactive zone (DRZ) and one distinct spot outside of the DRZ (termed X), which was detected in almost all placenta samples. We found total DNA adduct levels of 1.40 +/- 0.87 (0.04-3.65) and 1.04 +/- 0.63 (0.11-3.08) adducts per 10(8) nucleotides for the Teplice and Prachatice districts, respectively. The significant difference between both districts in placental DNA adduct levels was found for the winter sampling period only (1.49 vs. 0.96 adducts per 10(8) nucleotides; p = 0.023). No seasonal variation was observed for DNA adduct levels in the overall population studied. A positive GSTM1 genotype was detected in 51 subjects, while GSTM1-null genotype was found in 47 subjects. Higher DNA adduct levels were detected in a group with GSTM1-null genotype (p = 0.009). This finding seems more significant for subjects in the Teplice district (p = 0.047) than for those in the Prachatice district (p = 0.092). Significant district and seasonal differences were found in subgroups carrying the GSTM1-null genotype. DNA adduct levels in placentas of mothers with GSTM1-null genotype living in the polluted district of Teplice were higher than those in Prachatice (p = 0.050); also the adduct levels in placentas sampled in the summer period were higher than those sampled in the winter period (p = 0.011). Our results indicate that simultaneous analysis of DNA adducts and metabolic genotypes could emphasize the use of DNA adduct measurements, particularly in the case of the environmental exposure when the total doses of genotoxic pollutants are very low.
Keywords: polycyklické aromatické uhlovodíky; Pregnancy; Humans; městské obyvatelstvo; Radiography; Vitamin E; radiografie; Ascorbic Acid; Placenta; průmysl; Female; Vitamin A; dospělí; frekvence genu; Industry; lidé; Polycyclic Aromatic Hydrocarbons; Air Pollutants; Glutathione Transferase; látky znečišťující vzduch; Adult; kyselina askorbová; venkovské obyvatelstvo; vitamin A; roční období; ženské pohlaví; Seasons; těhotenství; Czech Republic; Gene Frequency; Rural Population; Smoking; Česká republika; placenta; kouření; glutathiontransferasa; adukty DNA; vitamin E; DNA Adducts; Urban Population